Approximate Analytical Study on a System of Non-Linear Partial Differential Equations in Chemical Science - Sathyapriya, B.; Ananthaswamy, V.; Jothi, J. Anantha (Communications in Mathematics and Applications, 2024)
Within a biofilter filled coupled with the woodchip-compost-blend, the biofiltration of mixtures containing toluene as well as n-propanol is discussed in this study. The chemical oxidation actions occurring within the gas and also biofilm phases, as well as the distribution of mass across the biofilm surface form the basis of the model’s structure. By employing a new homotopy perturbation approach, the semi-analytical outcomes for the n-propanol and toluene concentrations in non-dimensional form for the two phases have been found under time-dependent conditions for all appropriate experimental values of the parameters. Additionally, this study provides the MATLAB programming, which is employed as a numerical simulation for the problem. Through numerical simulation, the derived semi-analytical results are verified. The effects of several variables, such as non-dimensional constants for time-dependent conditions, are illustrated graphically